(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The increased use of multidrug-resistant (MDR) pathogens is a scenario that has required new therapeutic approaches to help increase the effectiveness of available antibiotics. This paper examines synergetic opportunities of Telfairia occidentalis (fluted pumpkin) leaf and seed extract to use with traditional antibiotics (such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa) to treat MDR bacterial strains. The study is assessed by in vitro analysis of minimum concentration of inhibition (MICs), fractional concentration indices (FICI), and time- Kill kinetics of such combinations. The findings show that Telfairia occidentalis extracts are highly effective in improving antibiotic efficacy as reductions in MICs reached up to 64-fold and synergetic FICIs (<0.5) were observed in three-quarters of interactions. The bioactive compounds that have been cited as the cause of this in the study include flavonoid and alkaloids, and mechanisms that have been proposed include efflux pump and membrane disruption. These results are important to highlight the opportunities of Telfairia occidentalis as an adjunct in the fight against MDR infections to fill important gaps in the treatment of antibiotic resistance. Clinical translation and subsequent phytochemical analysis recommendations are given.